The Apostasia genome and the evolution of orchids - Zhang, Guo-Qiang; Liu, Ke-Wei; Li, Zhen; Lohaus, Rolf; Hsiao, Yu-Yun; Niu, Shan-Ce; Wang, Jie-Yu; Lin, Yao-Cheng; Xu, Qing; Chen, Li-Jun; Yoshida, Kouki; Fujiwara, Sumire; et al. (Nature (London), 2017)
WebComparing the whole genome sequence of Apostasia shenzhenica with transcriptome and genome data from five orchid subfamilies permits the reconstruction of an ancestral gene toolkit, providing insight into orchid origins, evolution and diversification. Orchid origins Around 10 per cent of flowering plant species are orchids, with a broad diversity in both morphology and lifestyle. Apostasia is one of the earliest-diverging genera of Orchidaceae. To study the evolution and diversity of Orchidaceae, Zhong-Jian Liu, Yves Van de Peer and colleagues sequenced the genome of Apostasia shenzhenica , a self-pollinating species found in southeast China. The authors also report improved genomes for two species of Epidendroideae, Phalaenopsis equestris and Dendrobium catenatum , as well as transcriptome analysis of representatives of subfamilies of Orchidaceae. Their analyses provide insights into orchid origins, genome evolution, adaptation and diversification. Constituting approximately 10% of flowering plant species, orchids (Orchidaceae) display unique flower morphologies, possess an extraordinary diversity in lifestyle, and have successfully colonized almost every habitat on Earth 1 , 2 , 3 . Here we report the draft genome sequence of Apostasia shenzhenica 4 , a representative of one of two genera that form a sister lineage to the rest of the Orchidaceae, providing a reference for inferring the genome content and structure of the most recent common ancestor of all extant orchids and improving our understanding of their origins and evolution. In addition, we present transcriptome data for representatives of Vanilloideae, Cypripedioideae and Orchidoideae, and novel third-generation genome data for two species of Epidendroideae, covering all five orchid subfamilies. A. shenzhenica shows clear evidence of a whole-genome duplication, which is shared by all orchids and occurred shortly before their divergence. Comparisons between A. shenzhenica and other orchids and angiosperms also permitted the reconstruction of an ancestral orchid gene toolkit. We identify new gene families, gene family expansions and contractions, and changes within MADS-box gene classes, which control a diverse suite of developmental processes, during orchid evolution. This study sheds new light on the genetic mechanisms underpinning key orchid innovations, including the development of the labellum and gynostemium, pollinia, and seeds without endosperm, as well as the evolution of epiphytism; reveals relationships between the Orchidaceae subfamilies; and helps clarify the evolutionary history of orchids within the angiosperms.